Perlindungan Hukum Terhadap Pelayanan Kesehatan Tradisional di Indonesia - Nurani Ajeng Tri Utami; Nayla Alawiya (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2018)
Traditional health services in Indonesia have been regulated in the Law No. 36 of 2009 about Health and in Government Regulation No. 103 of 2014 specifically. This paper is intended to discuss the legal protection of traditional health services and its forms. This study applies normative juridical methods. The results show that the level of legal protection for traditional health services is empirically lower than complementary and integration. This is proven by the absence of the right to obtain legal protection for traditional empirical health services. The legality of traditional empirical health services is only attested by Traditional Health Registered Letters (STPT) while complementary and integration is attested by a Certificate of Traditional Health Worker Registration (STRTKT) and Practice Permit Traditional Health Workers (SIPTKT).